The constitutional crisis over the constitution (amendment) Bill, 1983 / Zainab Jan Abdul Ghafoor - Abdul Ghafoor, Zainab Jan (Faculty of Law, 1985)
The law is one of the most important characteristics to a country, because it enables that country to work out the administration and activities smoothly. Since a country and its people are not static and changes always take place, therefore amendments are necessary and are required from time to time. That is the feature of main-made law and only God's Law is complete and everlasting which needs no amendment to it. In Malaysia under Article 4(1) of the constitution says: “this constitution is the supreme law of the Federation and any law passed after Merdeka Day which is inconsistent with this constitution shall, to the extent of the inconsistency be void.’ The constitution is a solemn contract the product of intensive negotiations and bargaining between the Queen of England and the sultans on the one hand and the other communities on the other.